소아청소년기 간헐외사시 환자에서 사시수술 후 연령에 따른 과교정 회복기간 비교 - 조성원(Sung Won Cho), 하석규(Suk Gyu Ha), 김승현(Seung Hyun Kim) (Daihan angwa haghoi jabji, 2019)
목적: 소아청소년기 간헐외사시 환자에서 연령에 따른 수술 후 과교정 회복기간과 임상인자 간의 관계에 대하여 분석하였다. 대상과 방법: 기본형 간헐외사시로 양안 외직근후전술을 시행받은 환자의 의무기록을 후향적으로 조사하였다. 수술 전 연령, 성별, 사시각(prism diopters, PD), 원거리 억제 유무를 측정하였다. 수술 후 1일째 환자가 2 PD 이상 과교정이 있는 경우를 추적 관찰하였다. 과교정 회복은 사시각 검사 결과 정위의 획득으로 정의하였다. 환자는 10세 미만 군(1군), 10세 이상 군(2군)으로 나누어 분석하였다. 성공의 정의는 마지막 방문일 기준으로 10 PD 미만의 외편위, 5 PD 미만의 내편위를 보인 경우로 정의하였다. 결과: 88명의 환자가 포함되었다. 수술 후 1일째 원거리 사시각 -6.9 ± 2.2 PD (-12 to 0 PD), 근거리 사시각 -6.9 ± 2.4 PD (-12 to PD)을 보였다. 내편위는 음수로 표시하였다. 과교정 회복기간은 1.9 ± 3.9주(0-30주)였다. 수술 성공률은 71명(80.7%)에서 보였고, 1군과 2군의 수술 성공률은 유의한 차이를 보이지 않았다(p=0.51). 과교정 회복기간은 1군에서 1.8 ± 3.4주(1-30주), 2군에서 2.7 ± 5.9주(0-24주)로 유의한 차이를 보였다(p=0.02). 결론: 소아청소년기 간헐외사시 환자에서 연령에 따른 수술 성공률은 유의한 차이를 보이지 않았으나 10세 이상의 환자에서 과교정회복기간이 더 길 수 있다는 점을 유의해야겠다. Purpose: To investigate the recovery period of overcorrection and related factors after surgery in pediatric patients with basic intermittent exotropia (XT). Methods: Retrospective chart reviews of the medical records of patients who underwent bilateral lateral rectus recession for basic XT were analyzed. Preoperative age, sex, angle of deviation (prism diopters [PD]), and suppression at distance were measured. Patients were observed every week when the angle of deviation was > 2 PD of overcorrection at postoperative day 1. Recovery of overcorrection was defined as improvement of overcorrection with orthotropia. Patients were divided into two groups according to age: younger (group 1) and older (group 2) than 10 years of age. Success was defined as an angle of deviation between 10 PD of exodeviation and 5 PD of esodeviation at the final visit. Results: A total of 88 patients were included. At postoperative day 1, the angle of deviation at distance was -6.9 ± 2.2 PD, and the near angle of deviation was -6.9 ± 2.4 PD. Esodeviation presented as a minus value. The recovery period of overcorrection was 1.9 ± 3.9 weeks and the success rate was 80.7% (71 patients). The success rates of group 1 and group 2 were not statistically significant (p = 0.51). The recovery period of overcorrection in group 2 (2.7 ± 5.9 weeks) was significantly longer than in group 1 (1.8 ± 3.4 weeks) (p = 0.02). Conclusions: In pediatric adolescents with basic XT, the surgical success rates did not differ significantly according to age, but recovery of overcorrection after strabismus surgery took longer in patients ≥ 10 years of age. KCI Citation Count: 0